Analisis Yuridis Tanggung Jawab Notaris dalam Pembuatan Akta Otentik yang Mengandung Keterangan Palsu dari Para Pihak Berdasarkan Prinsip Kehati-Hatian - M. Diwani Adil Khuza (CV. ITTC INDONESIA, 2026)
A notary, as a public official, has the authority to create authentic deeds that have perfect evidentiary force. However, in practice, a deed may contain false information provided by the parties, potentially giving rise to legal disputes and liability for the notary. This study aims to examine the application of the precautionary principle by a notary and to analyze the notary's legal responsibility for deeds containing false information. This study uses a normative juridical method with a statutory and conceptual approach. The results show that the precautionary principle is applied through identity checks, document verification, and compliance with deed-making procedures in accordance with legal provisions. A notary is essentially only responsible for the formal truth of the deed, not the material truth of the parties' statements. However, if the notary is aware of or negligent regarding the existence of false information, the notary can be held accountable for administrative, civil, or criminal matters.